Definition of parameters for a test section for the analysis of natural convection and coolant loss in the AP1000 nuclear reactor by similarity laws and fractional scaling analysis - Luis Felipe Serra Cadiz; Mario Silva; Fernando Roberto de Andrade Lima; Carlos Alberto Oliveira (Brazilian Journal of Radiation Sciences)
The present work develops and analysis the main parameters of a test section for natural convection in case of failure of the pumping system as much as the loss of coolant in refrigeration accidents. For this realization a combination of laws of basic similarity and an innovative scale methodology, known as Fractional Scaling Analysis (FSA), was de-veloped. The depressurizing is analyzed when a rupture occurs in one of the primary system piping of the AP1000 nuclear reactor. This reactor is developed by Westinghouse Electric Co., which is a PWR (Pressurized Water Reactor) with an electric power equal to 1000MW. Such a reactor is provided with a passive safety system that promotes con-siderable improvements in the safety, reliability, protection and reduction of costs of a nuclear power plant. The FSA is based on two concepts: fractional scale and hierarchy. It is used to provide experimental data that generate quantita-tive evaluation criteria as well as operational parameters in thermal and hydraulic processes of nuclear power plants. The results were analyzed with the use of computational codes.